Database Reengineering and Interoperability
XIII, 350 p.
Keywords: Modern computing management systems and application programs are often de signed as open systems. In an open environment, the users' application programs serving similar purposes, though possibly implemented using different hardware or software tech nologies, can interact easily and properly with one other. But, it is a big challenge in research and development to provide the means for integrating these technologies and reengineering the new or existing management systems so as to make all of the relevant components interoperable. In case of databases, because of the variety in data models and theory, the interoper ability and reengineering issues become even more complex and crucial, especially for companies heavily involved in data management. With the rapid advances in networking and database modeling technology, old issues may have to be reinvestigated and new issues come up constantly. It is our hope that this year's workshop, the sixth in a series of annual events, can provide a timely forum for database researchers and practitioners to share their recent experience and results in various aspects of this fast -developing field. This series of workshops has been organized by the Hong Kong Computer Society and financially supported by many local industrial and business companies. This year, the Cooperative Research Centre for Open Systems Technology, located in the Department of Computer Science, City University of Hong Kong, has joined the organization team and the list of financial sponsors.